2018
DOI: 10.1038/s41598-018-33161-z
|View full text |Cite
|
Sign up to set email alerts
|

Improving carrier mobility of polycrystalline Ge by Sn doping

Abstract: To improve the performance of electronic devices, extensive research efforts have recently focused on the effect of incorporating Sn into Ge. In the present work, we investigate how Sn composition x (0 ≤ x ≤ 0.12) and deposition temperature Td (50 ≤ Td ≤ 200 °C) of the Ge1−xSnx precursor affect subsequent solid-phase crystallization. Upon incorporating 3.2% Sn, which is slightly above the solubility limit of Sn in Ge, the crystal grain size increases and the grain-boundary barrier decreases, which increases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 48 publications
4
67
0
Order By: Relevance
“…The electron mobility appears maximum value at Sn composition 0.04, which is slightly above the solubility of Sn in Ge. The result is consistent with the conclusion of GeSn semiconductor in the literatures [20,21]. Figure 9 shows that the Hall mobility is negative dependent on the carrier concentration, which identifies nonlinear.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The electron mobility appears maximum value at Sn composition 0.04, which is slightly above the solubility of Sn in Ge. The result is consistent with the conclusion of GeSn semiconductor in the literatures [20,21]. Figure 9 shows that the Hall mobility is negative dependent on the carrier concentration, which identifies nonlinear.…”
Section: Resultssupporting
confidence: 91%
“…SE has been used to investigate the electronic band structure. Moto et al reported that the maximum mobility for polycrystalline Ge 1-x Sn x alloys appeared at Sn composition 0.032 which was slightly above the solubility of Sn in Ge [21]. Researches also suggested that the hole mobility for polycrystalline Ge 0.984 Sn 0.016 alloy reached 540 cm V −1 s −1 [22].…”
Section: Introductionmentioning
confidence: 98%
“…For commercial applications, growth promotion is necessary using a method such as adding Sn in Ge. 38,39 In conclusion, Sb doping into an a-Ge precursor significantly influenced the subsequent SPC. The Sb doping on the order of 10 20 cm À3 facilitated the SPC and increased the grain size of the resulting Ge layer.…”
mentioning
confidence: 90%
“…A similar behavior has also been reported in Sndoped SPC-Ge. 38,39 Conversely, for C Sb ¼ 5.0 Â 10 20 cm À3 , both nucleation and lateral growth rates are lower than those of undoped Ge. Therefore, for C Sb ¼ 5.0 Â 10 20 cm À3 , the grain size enlargement [ Fig.…”
mentioning
confidence: 92%
“…Ge 1−x Sn x has attracted much research interest as an exciting material with potential applications in nextgeneration rechargeable lithium-ion battery anodes and optoelectronic devices, due to their high carrier mobilities [1][2][3] and a direct band gap which can be tuned by varying the tin concentration [4][5][6][7][8][9][10][11][12]. Additionally, cubic Ge 1−x Sn x allows the lattice dimensions to be tuned over a wide range, which is beneficial when used as a buffer layer to reduce strain arising from lattice mismatch between III-V or II-VI compounds with silicon or germanium substrates [13][14][15].…”
Section: Introductionmentioning
confidence: 99%